Moisture and Compression Properties of Different Composition of Kenaf/Bamboo/Polyester Thermal Bonded Nonwoven Web for Mattress Filler - Zulhizad, Noraishah; Abdul Rashid, Azrin Hani; Abd Haris, Nurul Arisya; Shaari, Muhammad Farid; Mohd Rosli, Mohd Afzanizam; A Rashid, Ahmad Safuan; Mohd Tahir, Abdussalam Al-hakimi; Rajput, Abdul Waqar (International Journal of Integrated Engineering, 2024)
This study assesses the performance of kenaf, bamboo, and polyester nonwoven web in various mattress filling formulations.  The influence of moisture and compression qualities on the web structure with a predefined thickness and the number of stacking layers is evaluated. Carding and thermal bonding techniques were employed to create the kenaf/bamboo/polyester web. Physical properties such as thickness (ASTM D177-96), areal weight (ASTM D6242), density (ASTM D3776), and moisture content (ASTM D2495-01) were determined, while the compressive performance was evaluated according to ASTM D471-00. Compressive strength decreased with higher ratios of untreated bamboo to kenaf, whereas moisture content increased with both higher kenaf and treated bamboo ratios. The compressive strength of kenaf/bamboo/polyester nonwoven web was minimally impacted by the treated bamboo. Consequently, the areal weight and density of the web were significantly influenced by a predetermined characteristic; the number of stacking layers and thickness of the web. Evidence suggests that a composition of 30% kenaf, 20% bamboo and 50% polyester is the optimal ratio to obtain the firmest mattress filler, as it exhibited a compressive percentage of 39% at a force of 2kN.